1992
DOI: 10.1002/j.1460-2075.1992.tb05526.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor receptor-4 shows novel features in genomic structure, ligand binding and signal transduction.

Abstract: Fibroblast growth factor (FGF) receptor (FGFR) gene family consists of at least four receptor tyrosine kinases that transduce signals important in a variety of developmental and physiological processes related to cell growth and differentiation. Here we have characterized the binding of different FGFs to FGFR‐4. Our results establish an FGF binding profile for FGFR‐4 with aFGF having the highest affinity, followed by K‐FGF/hst‐1 and bFGF. In addition, FGF‐6 was found to bind to FGFR‐4 in ligand competition exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(94 citation statements)
references
References 42 publications
5
89
0
Order By: Relevance
“…Among the four receptors, FGFR-1 and 2 have a high a nity for FGF-2 (Dionne et al, 1990). In contrast, FGFR-3 preferentially binds FGF-1 (Ornitz and Leder, 1992), and FGFR-4 binds FGF-1 with high a nity but shows low a nity for FGF-2 (Vainikka et al, 1992). Cell transformation upon FGF-2 addition has been described in ®broblasts overexpressing FGFR-1 (Bernard et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Among the four receptors, FGFR-1 and 2 have a high a nity for FGF-2 (Dionne et al, 1990). In contrast, FGFR-3 preferentially binds FGF-1 (Ornitz and Leder, 1992), and FGFR-4 binds FGF-1 with high a nity but shows low a nity for FGF-2 (Vainikka et al, 1992). Cell transformation upon FGF-2 addition has been described in ®broblasts overexpressing FGFR-1 (Bernard et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…FGFRlIIIb binds efficiently to aFGF, FGF3 and FGF 10, while FGFRl Ilk binds to aFGF, bFGF, FGF4, FGF6, FGF8 and FGF9 (Ornitz et al, 1996). FGFRl-3 demonstrate both IIIb and IIIc splice variant isoforms, but FGFR4 is unique and has no IIIb splice variant, being expressed as the IIIc isoform only (Johnson et al, 1991;Vainikka et al, 1992;Chellaiah et al, 1994).…”
mentioning
confidence: 99%
“…We don't know the level of expression of FGFR-3 or -4 in these two cell lines but it should be underlined that these two FGF receptors would not contribute to bind FGF-2 e ciently. In fact, FGFR-3/IIIb, the only FGFR-3 variant expressed by the epithelial cells binds only FGF-1 (Chellaiah et al, 1994), while FGFR-4 binds FGF-1 with high a nity but shows low a nity for FGF-2 (Vainikka et al, 1992). Along this line, we have observed that when NBT-II cells, stably transfected with expression vector encoding the human FGFR-1 (WennstroÈ m et al, 1991) or the human IIIc variant of the FGFR-2 (Houssaint et al, 1990), were treated with exogenous FGF-2, they showed a mixture of IIIb and IIIc transcripts and they became dissociated (our unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the FGFR-4 gene was shown to lack two alternative exons for Ig domain 3 and to contain only exon IIIc. This FGFR-4 binds FGF-1 with high a nity but shows low a nity for FGF-2 (Vainikka et al, 1992).…”
Section: Introductionmentioning
confidence: 99%